Pattern of Bone Mineral Density (BMD) Among Patients Attending Tertiary Hospital: 9 years’ Experience (Bangladesh Journal of Nuclear Medicine, 2017)
Objective: A retrospective study was conducted to assess the pattern of bone density status in a large population of both sexes who attended tertiary hospital National Institute of Nuclear Medicine and Allied Sciences (NINMAS) in a specific time period.Materials and Methods: A retrospective study was carried out on 2777 patients who were referred to NINMAS for dual energy X- ray absorptiometry (DXA) measurement of bone mineral density (BMD) during the year March 2005 to January 2014. BMD was measured at femoral neck (Ward’s triangle) and lumbar spines with a Norland XR-36 machine. Data about age, sex, body weight, presentations, back pain status and menstrual history were recorded. Few of them had known osteoporosis and history of fracture. Reporting was done according to the T score following WHO criteria. Few reports were based on the Z-score.Results: A total of 2777 (M=788, F=1989 with a ratio of 1: 2.5) patients with age ranging from 12 to 85 (mean + SD 43 + 11.1). BMD findings and relevant history were recorded. Results showed normal bone density in 478 (17.21%), osteopenia in 866 (31.18%), osteoporosis in 1108 (39.91%) and discrepancy of BMD in hip and spine in 325 (11.70%) patients. Female patients (n=1989) were sub divided into 6 sub groups according to age range and significant relationship of bone loss with pre peri and postmenopausal status of women were observed. These 6 groups included women of 25-34 years, 35-44years, 45-54 years, 55-64 years, 65-74 years and 75-85 years. Among them, the largest subgroups of 845 (42.4%) were of 55-64 years and maximum number (54.9%). of osteoporosis cases were of this age range. About 70% patients experienced low back pain with variable severity and duration. Mean body weight (± SD) among the premenopausal women was 49.9 ± 9.4 Kg and 48.2 ± 10.8 kg in postmenopausal women.Conclusion: The results of this study suggest that advancing age and menopausal condition of female and low body weight are important risk factors for the occurrence of low BMD.Bangladesh J. Nuclear Med. 18(1): 47-50, January 2015